Structural evolution of the El Salvador Fault Zone: an evolving fault system within a volcanic arc. - Canora, Carolina; Martínez-Díaz, José J.; Villamor, Pilar; Staller, Alejandra; Berryman, Kelvin; Álvarez-Gómez, Jose A.; Capote, Ramón; Diaz, Manuel (Journal of Iberian Geology, 2014)
The El Salvador Fault Zone, firstly identifiedafter the 13th February 2001 Mw 6.6 El Salvador earthquake, is a 150 km long,20 km wide right-lateral strike-slip fault system. Ruptures along the ESFZ arethought to be responsible for most of the historical destructive earthquakesalong the El Salvador Volcanic Arc, as well as for most of the currentseismicity of the area. In this work, we focus on the geological setting of thefault zone by describing its geomorphology and structure, using field-based observations,digital terrain modelling, and aerial photograph interpretation with the aim atcontributing to the understanding of the ESFZ slip behaviour. In particular, weaddress the ESFZ structure, kinematics and evolution with time. The ESFZ is a complex set of traces divided inmajor rupture segments characterized by different geometry, kinematics andgeomorphic expressions. Natural fault exposures and paleoseismic trenchesexcavated along the fault show that the strike slip deformation is distributedin several planes. Both geometry and kinematics of the fault zone areconsistent with a transtensional strain regime.The estimated geological slip-rate for the mainfault segments by paleoseismic trenches and displaced geomorphic features impliesa deficit in velocity of the fault compared to the available GPS velocitiesdata. The high vertical scarps of some fault segments would require quaternaryslip rates not coherent neither with measured GPS velocities nor with sliprates obtained from paleoseismic analysis. This mismatch suggests apre-existing graben structure that would be inherited from the previousregional roll back related extensional stage. We consider that the ESFZ isusing this relict structure to grow up along it. As a result, we propose amodel for ESFZ development consistent with all these observations.